KIF13B C.*3163G>A SINGLE NUCLEOTIDE VARIANT ON OROPHARYNGEAL SQUAMOUS CELL CARCINOMA SUSCEPTIBILITY AND TUMOR CHARACTERISTICS - Ericka Francislaine Dias Costa; Gustavo Jacob Lourenço; Carmen Silvia Passos Lima (Hematology, Transfusion and Cell Therapy)
Introduction/Justification: Oropharyngeal squamous cell carcinoma (OPSCC) is a subtype of head and neck cancer with high mortality rates and aggressive behavior. Smoking, alcohol consumption, and HPV infection are well-established risk factors in carcinogenesis of the tumor. Genetic inherited variations can influence OPSCC susceptibility and tumor characteristics by altering gene expression. The KIF13B gene encodes a kinesin motor protein involved in intracellular transport, and sequence variations in its regulatory regions may affect gene expression. However, the impact of the KIF13B c.*3163G>A single nucleotide variant (SNV) on OPSCC risk and tumor features remains unclear. Objectives: To evaluate whether distinct genotypes of the SNV KIF13B c.*3163G>A influence the risk and tumor characteristics of OPSCC, as well as the expression of the KIF13B gene and the microRNA (miRNA) let-7e-3p in controls, and to functionally assess the interaction between let-7e-3p and the SNV region in the 3’-UTR of KIF13B. Materials and Methods: We evaluated 250 OPSCC patients and 250 controls seen at the Clinical Oncology Services of the General Hospital of University of Campinas. The genomic DNA was obtained from peripheral blood leukocyte samples from patients and controls entered the study. The KIF13B c.*3163G>A SNV genotypes were identified by polymerase chain reaction (PCR). The RNA was obtained from peripheral blood leukocyte samples from controls. The gene and let-7e-3p expression were evaluated by quantitative PCR. Interaction between let-7e-3p and the 3’-UTR of KIF13B was evaluated by luciferase reporter assay in FaDu and Detroit 562 pharyngeal cell lines. Results: KIF13B c.*3163GG genotype was more common in OPSCC patients than in controls (42% versus 32%; P = 0.03); individuals with KIF13B c.*3163GG genotype were under 1.73-fold increased risk of OPSCC than others. KIF13B c.*3163GG genotype was more common in patients with greater tumor extension (46% versus 28%, P = 0.01) than others and in patients with greater tumor extension than in controls (46% versus 32%; P = 0.004); individuals with KIF13B c.*3163GG genotype were under 2.47-fold increased risk of aggressive OPSCC than others. Individuals with KIF13B c.*3163GG genotype showed lower levels of KIF13B mRNA (1.02 arbitrary units (AUs) ± 0.35 standard deviation (SD) versus 1.28 AUs ± 0.53 SD, P = 0.05). The expression level of miRNA let-7e-3p was similar in individuals with distinct genotypes KIF13B c.*3163G>A SNV (0.52AUs ± 0.31DP versus 0.48AUs ± 0.26DP versus 0.55AUs ± 0.39DP, respectively; P= 0.85). The let-7e-3p miRNA exhibited more efficient binding to the 3’-UTR of the ancestral G allele compared to the variant A allele in the FaDu (p = 0.004) and Detroit 562 (p = 0.04) cell lines. Conclusion: Our data present, for the first time, evidence that KIF13B c.*3163G>A SNV is associated with increased risk of OPSCC possibly due to the variation of KIF13B gene expression, modulated by the miRNA let -7e-3p. Acknowledgements: The study was supported by the Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq) (grant number 140026/2015-0), Postdoctoral Program (PPPD) at the University of Campinas (UNICAMP) (Postdoctoral ID number: 326285), and the Fundação de Apoio ao Ensino e à Pesquisa do Estado de São Paulo (FAPESP) Cancer Theranostics Innovation Center (CancerThera) (FAPESP 2021/10265-8).